Da Arqueoastronomia e da Etno-Antropologia – Contributo para uma Epistemologia do Estudo da(s) Lógica(s) das Sociedades Camponesas - Fitas, Ana Paula (Trabalhos de Antropologia e Etnologia, 2020)
Given the recurrent relationship between Archeology and Astronomy, this article proceeds to an epistemological approach from this traditional and persistent ethno-anthropological perspective, proposing, for this goal, an integrated reading of symbolic thought associated with the astronomical dimension and material culture of societies that preceded the written records of History. The author uses a case study, exemplifying it with the megalithic area of Alentejo located in Évora district.